MiR‐126 Contributes to Human Umbilical Cord Blood Cell‐Induced Neurorestorative Effects After Stroke in Type‐2 Diabetic Mice. (January 2016) - Chen, Jieli; Ning, Ruizhuo; Zacharek, Alex; Cui, Chengcheng; Cui, Xu; Yan, Tao; Venkat, Poornima; Zhang, Yi; Chopp, Michael
Abstract : Diabetes mellitus (DM) is a high risk factor for stroke and leads to more severe vascular and white‐matter injury than stroke in non‐DM. We tested the neurorestorative effects of delayed human umbilical cord blood cell (HUCBC) treatment of stroke in type‐2 diabetes (T2DM). db/db‐T2DM and db/+‐non‐DM mice were subjected to distal middle cerebral artery occlusion (dMCAo) and were treated 3 days after dMCAo with: (a) non‐DM + Phosphate buffered saline (PBS); (b) T2DM + PBS; (c) T2DM + naïve‐HUCBC; (d) T2DM + miR‐126 −/− HUCBC. Functional evaluation, vascular and white‐matter changes, neuroinflammation, and miR‐126 effects were measured in vivo and in vitro. T2DM mice exhibited significantly decreased serum and brain tissue miR‐126 expression compared with non‐DM mice. T2DM+HUCBC mice exhibited increased miR‐126 expression, increased tight junction protein expression, axon/myelin, vascular density, and M2‐macrophage polarization. However, decreased blood‐brain barrier leakage, brain hemorrhage, and miR‐126 targeted gene vascular cell adhesion molecule‐1 and monocyte chemotactic protein 1 expression in the ischemic brain as well as improved functional outcome were present in HUCBC‐treated T2DM mice compared with control T2DM mice. MiR‐126 −/− HUCBC‐treatment abolished the benefits of naïve‐HUCBC‐treatment in T2DM stroke mice. In vitro, knock‐in of miR‐126 in primary cultured brain endothelial cells (BECs) or treatment of BECs with naïve‐HUCBCs significantly increased capillary‐like tube formation, and increased axonal outgrowth in primary cultured cortical neurons; whereas treatment of BECs or cortical neurons with miR‐126 −/− HUCBC attenuated HUCBC‐treatment‐induced capillary tube formation and axonal outgrowth. Our data suggest delayed HUCBC‐treatment of stroke increases vascular/white‐matter remodeling and anti‐inflammatory effects; MiR‐126 may contribute to HUCBC‐induced neurorestorative effects in T2DM mice. Stem Cells 2016;34:102–113